Clinical Relevance of Nuclear Magnetic Resonance LipoProfile - Emeasoba, Emmanuel U.; Ibeson, Emeka; Nwosu, Ifeanyi; Montemarano, Nadine; Shani, Jacob; Shetty, Vijay S. (Frontiers in Nuclear Medicine, 2022)
Identifying risk factors for cardiovascular diseases in patients is key to reducing their resulting morbidity and mortality. Currently, risk factors are assessed using parameters that include and emphasize the role of the level of cholesterol carried by lipoproteins. Most providers focus on targeting cholesterol levels in patient management. However, recent research shows that lipoprotein particle number is more predictive of cardiovascular risk than cholesterol levels. The Nuclear Magnetic Resonance (NMR) LipoProfile test assesses the number of lipoprotein particles, sizes of lipoproteins, levels of cholesterol, and patient risk categories. Furthermore, it enables the identification of patients with underestimated cardiovascular risks – those with a discordant high number of low-density lipoprotein (LDL) particles (LDL-P) despite low cholesterol levels. While the NMR LipoProfile test requires a higher cost and longer waiting time for results in comparison to the lipid panel test, its advantages cannot be ignored. This review article focuses on exploring the routine use of NMR LipoProfile in clinical practice.